2006
DOI: 10.1128/jvi.01272-06
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Virus Infection of Primary Neuronal Cultures and Adult Mice: Failure To Demonstrate Evidence of Excitotoxicity

Abstract: Cultures derived from the cerebral cortices and hippocampi of 17-day-old mouse fetuses infected with the CVS strain of rabies virus showed loss of trypan blue exclusion, morphological apoptotic features, and activated caspase 3 expression, indicating apoptosis. The NMDA (N-methyl-D-aspartate acid) antagonists ketamine (125 M) and MK-801 (60 M) were found to have no significant neuroprotective effect on CVS-infected neurons, while the caspase inhibitor Ac-Asp-Glu-Val aspartic acid aldehyde (25 M) exerted a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…This would also pave the way for future studies of the determinism of the apparent, straindependent neuronal selectivity exhibited by these agents (17). Primary nerve cell cultures have proved their usefulness for the evaluation of therapeutic compounds in neurodegenerative or infectious diseases (15,52,57). Here, we addressed the relevance of scrapie-infected primary nerve cell cultures as a potential model for the evaluation of antiprion molecules by using three different compounds that were previously described to clear PrP res in chronically infected cell lines but presented inconsistent prophylactic and therapeutic activities in vivo (51).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This would also pave the way for future studies of the determinism of the apparent, straindependent neuronal selectivity exhibited by these agents (17). Primary nerve cell cultures have proved their usefulness for the evaluation of therapeutic compounds in neurodegenerative or infectious diseases (15,52,57). Here, we addressed the relevance of scrapie-infected primary nerve cell cultures as a potential model for the evaluation of antiprion molecules by using three different compounds that were previously described to clear PrP res in chronically infected cell lines but presented inconsistent prophylactic and therapeutic activities in vivo (51).…”
Section: Discussionmentioning
confidence: 98%
“…They make an individual living cell with a phenotype very close to the in vivo one accessible for local application of pharmacological compounds or neurotropic infectious agents and allow morphological studies of, for example, neuronal connectivity and viability. As such, primary neuronal cultures are valuable tools routinely used for neurotrophic and antiapoptotic drug evaluation in neurodegenerative as well as infectious diseases (15,35,52,57).…”
mentioning
confidence: 99%
“…Excitotoxicity has been studied in rabies virus-infected primary neuron cultures and in an experimental mouse model of rabies without any supporting evidence that excitotoxicity plays an important role in neuronal dysfunction or death. 34 Early in vivo studies by Prosniak et al 35 in mice using subtraction hybridization showed that infection with fixed rabies virus resulted in downregulation of about 90% of genes at more than four-fold lower levels in comparison with the normal brain. In contrast, only about 1.4% of genes became upregulated, including genes involved in regulation of cell metabolism, protein synthesis, and growth and differentiation.…”
Section: Mechanisms For Neuronal Dysfunction and Deathmentioning
confidence: 99%
“…4 In the early phases, infection seems to induce severe neuronal dysfunction, but little corresponding neuronal cytopathic damage. 15,16 Since the pathophysiology of rabies virus infection appears to be primarily neuronal dysfunction rather than inflammation and cell death, the clinical syndrome of rabies encephalitis is theoretically reversible. A fundamental requirement for recovery would be viral clearance and development of a protective immune response.…”
Section: Clinical Managementmentioning
confidence: 99%